INAPTED BODIES: THE SOCIAL IMPACTS OF THE EPIDEMICS OF MALARIA, DENGUE, CHIKUNGUNYA AND ZIKA IN BRAZIL. (Fiep Bulletin - online, 2019)
The objective of this study is to analyze the social impacts of malaria, dengue, chikungunya and zika epidemics inBrazil. Understand how so-called neglected diseases and their overwhelming epidemics compromise the social development ofthe population by producing unfit bodies. During decades of the twentieth century, malaria constantly left unfit men, women andchildren, at the end of the same century the epidemics of dengue in the hottest year seasons disfavoured sporadically the bodiesof Brazilians. In the 21st century, new epidemics such as chikungunya and zika temporarily marked and in some cases definitelythe bodies of our society. The historical knowledge of the structures and operations of control, treatment and fight against theepidemics that have protagonists the mosquitoes can help us to face new epidemics that found in the urban space anenvironment conducive to its development partly explained by the lack of information, policies prevention and neglect of publicauthorities. In this sense, the evaluation of the social impacts of epidemics is fundamental for the construction of projects that aimat human development in all its spheres: social, political and economic.